ANALISIS KEBIJAKAN PROGRAM MAKAN BERGIZI GRATIS SEBAGAI INSTRUMEN INTERVENSI GIZI DALAM PENANGGULANGAN STUNTING - Karmanis; Ainun Ganisia; Ruri Fintayana (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2026)
Stunting is a chronic nutritional problem that has long-term impacts on the quality of human resources in Indonesia, particularly in Pemalang Regency, Central Java. The government has implemented various nutrition intervention policies, one of which is the Free Nutritious Meal Program (MBG) as an effort to improve the nutritional status of the population, especially school-age children, toddlers, and pregnant women. This study aims to analyze the policy of the Free Nutritious Meal Program (MBG) as a nutrition intervention instrument in stunting prevention. This research uses a qualitative approach with a descriptive-analytical method. Data were collected through interviews, observations, and documentation involving informants from the Health Office, Education Office, schools, health workers, posyandu cadres, and beneficiary communities. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The validity of the data was tested through source and method triangulation The results show that the MBG program has a positive impact in improving community access to nutritious food, enhancing children’s dietary patterns, and increasing parents’ nutrition awareness. The program also strengthens cross-sector collaboration between local government, schools, and health facilities in efforts to reduce stunting. However, the implementation of the program still faces several challenges, such as limited supervisory personnel, budget constraints, uneven distribution, and low nutrition literacy among the community. In addition, the effectiveness of the program in significantly reducing stunting rates still requires long-term evaluation due to the multidimensional nature of stunting determinants. In conclusion, the Free Nutritious Meal Program has strong potential as a nutrition intervention policy instrument in stunting prevention in Pemalang Regency. However, its success largely depends on strengthening governance, cross-sector coordination, capacity building, and policy sustainability. Therefore, integration with other health and social intervention programs is needed to achieve optimal stunting reduction.